3D printing of PEEK-based medical devices (Transactions on Additive Manufacturing Meets Medicine, 2019)
A potential clinical concern about polyetheretherketone (PEEK) is that it is not bioactive enough, and thus has limited fixation to bone. To overcome this problem, bioactive materials and/or porosity are incorporated into PEEK medical devices. The latest developments in these two strategies are presented in this paper. Bioactive PEEK/HA prepared by integration of 3D printing and compression molding is presented in this paper. In addition, nozzle and build plate temperatures for 3D printing of porous PEEK were optimized using genetic algorithm to achieve the highest mechanical strength for load bearing applications such as spinal fusion cages